International branch campuses as an entry mode to the foreign education market - Egle Girdzijauskaite; Asta Radzeviciene; Arturas Jakubavicius; Audrius Banaitis (Administrative Sciences, 2019)
Higher education institutions (HEIs), especially latecomer institutions, continue to regard exporting education services by creating a commercial presence in a foreign country with caution. The purpose of this paper is to investigate ways of creating and managing international branch campuses (IBCs) and to elaborate recommendations for universities on establishing a branch campus as an entry into the foreign education market. In order to reach this aim, we analyse the trends of IBC development in higher education in the last 30 years, compare the theory and concepts of service export in business and in higher education and, finally, conduct a case study on seven IBCs globally. The analysis shows clear synergy between business theory and higher education (HE); however, no obvious coherence is discovered between the IBC establishment practices and the traditional Uppsala internationalisation model used in international business practices. This research continues by verifying the coherence of IBCs with the revisited Uppsala model based on the relationships and market commitment.
Keywords: 350; international branch campus; internationalisation; foreign market; entry mode